FORAGE AND GRAIN YIELD OF SOME BARLEY GENO TYPES UNDER RAIN-FED CONDITIONS - Abbas M. Al Hasan (Mesopotamia Journal of Agriculture)
This study was carried out during three growing seasons , 1999-2000, 2000-2001 , 2001-2002 at Nineva Agriculture Experimental Station at Al-Rasheedia to compare forage and grain yield of Barley genotypes namely ; local Black , Rehan , Jazeera 1, select 11 , 21 and 31.Genotype did not differed significantly from each other in green forage yield , While there was a significant differences among strain in hay , silage , straw and grain yield and with superiority of selected strains over cultivated varieties in these studied characters . Forage and grain yield of genotypes significantly differed from season to other with seasonal variation in rainfall quantity and its distribution . Interaction between genotypes & growing seasons significantly affected all studied character with exception of green forage yield . genotype have law stability value for all studied characters ,with exception of that for green forage yield .